EFL LEARNERâS SELF âREGULATED LEARNING STRATEGIES IN ACHIEVING AN EXCELLENT ACADEMIC PERFORMANCE - M, Sofyan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2017)
The study investigated strategies employed by a successful student taking on his undergraduate degree in one of the best universities in Makassar. The purpose of the study is to increase understanding and knowledge of self-regulated learning and regulation strategies as part of the affective factors of EFL Learning. The study which was a single case was investigated by using qualititave approach. Data was collected thorugh technology assissted interview practicing an open ended conversation and questions. The result of analysis revealed that he utilized the following types of strategies to perform his self-regulation : a) forethought phase for example, setting academic goal, planning, keeping self-efficay, keeping motivation; b) performance phase, such as, organizing, seeking information, keeping records and monitoring, structuring environment; b) self-reflection phase, such as, self consequences, seeking social assisstance, reviewing records, and self evaluation.